2021
DOI: 10.1556/2060.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum hepcidin levels and cardiovascular disease in patients with maintenance hemodialysis

Abstract: BackgroundTo investigate the serum level of hepcidin and its relationship with cardiovascular disease (CVD) in maintenance hemodialysis (MHD) patients.MethodsBlood was obtained from 75 MHD patients before undergoing hemodialysis and 20 healthy controls. Serum hepcidin, advanced oxidation protein products (AOPP) and interleukin (IL)-6 were measured by enzyme-linked immunosorbant assay (ELISA). Spearman correlation, and binary logistic regression linear regression analyses were used to assess the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…8 Previous studies demonstrated that hepcidin-25 could help to evaluate the iron status and anemia, 9,10 and participated in the pathophysiology of atherosclerosis and cardiovascular events in patients receiving MHD. 11,12 However, one study of 56 patients receiving MHD showed that serum hepcidin-25 could not predict the hematopoietic response to the therapy of intravenous iron plus erythropoiesis-stimulating agent (ESA). 13 A similar conclusion was reported in another study of 61 patients with nondialysis chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies demonstrated that hepcidin-25 could help to evaluate the iron status and anemia, 9,10 and participated in the pathophysiology of atherosclerosis and cardiovascular events in patients receiving MHD. 11,12 However, one study of 56 patients receiving MHD showed that serum hepcidin-25 could not predict the hematopoietic response to the therapy of intravenous iron plus erythropoiesis-stimulating agent (ESA). 13 A similar conclusion was reported in another study of 61 patients with nondialysis chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that hepcidin, an iron regulator, was associated with absolute and functional iron deficiency [18]. Additionally, hepcidin was associated with high rates of cardiovascular disease or mortality via direct or indirect pathways in patients undergoing dialysis [19][20][21][22]. Iron overload is associated with cellular damage via the generation of reactive oxygen species, which leads to adverse events such as premature death or atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%